Distant heart eaudiobook Westward hearts series, book 2. - Bateman, Tracey V. (Westward Hearts, 2008)
Award-winning author Tracey Bateman touches hearts with her uplifting historical novels. In this sweeping sequel to Defiant Heart, godly scout Sam Two Feathers and born-again fancy-girl Toni Rodden despair of finding true love along the 1850 Oregon Trail. Who would marry a half-breed or a former harlot? "A wonderful story of adventure and love ..."-Tracie Peterson